2003
DOI: 10.3363/prb1992.16.0_11
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Martotriose With Inorganic Cyclo-Triphosphate

Abstract: The phosphorylation of maltotriose by cyclo-triphosphate (P3m) proceeded on not only 1-OH group of a reducing unit, but also 2,-OH and 2,,-OH of nonreducing units in aqueous solution. The optimum condition for the phosphorylation of maltotriose with P3m was a molar ratio of P3m : maltotriose = 1 : 4, pH 12, and 25•Ž.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Previously, we reported that alkylamines 8 , amino acid 9 , aminoalcohols 10 , and carbohydrates [11][12][13][14][15][16] readily phosphorylated with P 3m to give their triphosphate derivatives. Organic compounds containing amino or hydroxyl group were easily phosphorylated by P 3m .…”
Section: Structure Of Theanine (Thea)mentioning
confidence: 99%
“…Previously, we reported that alkylamines 8 , amino acid 9 , aminoalcohols 10 , and carbohydrates [11][12][13][14][15][16] readily phosphorylated with P 3m to give their triphosphate derivatives. Organic compounds containing amino or hydroxyl group were easily phosphorylated by P 3m .…”
Section: Structure Of Theanine (Thea)mentioning
confidence: 99%
“…The main phosphorylated products were 2Ј-and 3Ј-monophosphate esters of the nucleosides and nucleotides. We also reported that alkylamines, 11) aminoalcohols, 12) and carbohydrates [13][14][15][16][17][18] are readily phosphorylated with P 3m to give the corresponding triphosphate derivatives. Unfortunately, phosphorylated carbohydrates are easily decomposed to monophosphate derivatives.…”
mentioning
confidence: 99%
“…Unfortunately, phosphorylated carbohydrates are easily decomposed to monophosphate derivatives. 9,10,[13][14][15][16][17][18] We have developed new inorganic phosphorylating reagents, imido-cyclo-triphosphates, Na 3 P 3 O 9Ϫn (NH) n . Compared with the P-O-P linkage, the P-NH-P linkage is stable and difficult to hydrolyze.…”
mentioning
confidence: 99%
“…[3][4][5] This reaction was found to be applicable to other monosaccharides and oligosaccharides. [6][7][8] Unfortunately, the products formed from carbohydrates are easily decomposed to monophosphate derivatives.Imido-cyclo-triphosphates, Na 3 P 3 O 9Ϫn (NH) n , have been known since 1962. 9) Compared with the P-O-P linkage, the P-NH-P linkage is stable and difficult to hydrolyze.…”
mentioning
confidence: 99%
“…Previously, we reported that alkylamines, 1) aminoalcohols, 2) and carbohydrates [3][4][5][6][7][8] are readily phosphorylated with P 3m to give their triphosphate derivatives. In particular, the reaction of D-glucose with P 3m in aqueous solution afforded 1-O-triphospho-b-D-glucose stereoselectively in good yield (47%) in a one-step process without protection of hydroxyl groups.…”
mentioning
confidence: 99%